Intraoperative or postoperative stereotactic radiotherapy for brain metastases: time to systemic treatment onset and other patient-relevant outcomes - Dejonckheere, Cas S.; Layer, Julian P.; Hamed, Motaz; Layer, Katharina; Glasmacher, Andrea; Friker, Lea L.; Potthoff, Anna-Laura; Zeyen, Thomas; Scafa, Davide; Koch, David; Garbe, Stephan; Holz, Jasmin A.; et al. (Journal of neuro-oncology, 2023)
Intraoperative radiotherapy (IORT) has become a viable treatment option for resectable brain metastases (BMs). As data on local control and radiation necrosis rates are maturing, we focus on meaningful secondary endpoints such as time to next treatment (TTNT), duration of postoperative corticosteroid treatment, and in-hospital time.
Online veröffentlicht: 9. Oktober 2023
Gesehen am 15.07.2024